Automated Cloud Migration System for Permissioned Blockchain Infrastructure - Annisa, Faradiba; Bhawiyuga, Adhitya; Akbar, Sabriansyah Rizqika; Shaffan, Nur Hazbiy; Kartikasari, Dany Primanita (Journal of Information Technology and Computer Science, 2025)
Blockchain is a technology that stores data in a distributed manner. There are two types of blockchains: permissionless and permissioned. In permissionless blockchains, nodes are operated by anonymous participants who do not know each other. Meanwhile, permissioned blockchain nodes run on a private infrastructure owned by the organizations participating in the blockchain network. This infrastructure may need to be migrated for various reasons, either from on-premises to the cloud or between clouds. Therefore, in this research, a migration system for permissioned blockchain infrastructure is developed. This migration system operates automatically to reduce human errors, inconsistencies, and time inefficiencies. To achieve automation, Infrastructure as Code (IaC) and automation tools are used. The IaC tool is used to automate infrastructure provisioning on the target cloud platform, while the automation tool is used to configure and deploy the blockchain on virtual machines in the target cloud. The chosen cloud platform is a public cloud. The experiment on the automated migration system focuses on two aspects. The first aspect evaluates the system's capability to perform infrastructure provisioning, blockchain configuration, and blockchain deployment on the target cloud platform. The second aspect assesses the migrated blockchain's functionality compared to the source infrastructure. The experimental results demonstrate that the automated migration system can successfully provision infrastructure, configure, and deploy the blockchain on virtual machines in the target cloud. Furthermore, the results confirm that the blockchain on the target infrastructure can add new data and access previously generated data within the blockchain.